Scientific Mapping of Research on Parenting Practices and Child Nutrition Based on Bibliometric Analysis - Rastra Hammasa Rafiquraya; Titih Huriah (Universitas Pahlawan Tuanku Tambusai, 2026)
Parenting practices play a crucial role in shaping children’s eating behaviors and nutritional outcomes. This study aimed to map the scientific landscape of research on parenting practices and child nutrition using a bibliometric approach. Data were collected from the Scopus database and supported by Web of Science using the keywords “parenting practices” and “nutrition.” Following the PRISMA process, 928 documents were initially identified and filtered based on publication year (2015–2025), subject area (Medicine and Nursing), document type (articles and reviews), and English language, resulting in 475 eligible publications. Bibliometric analysis was conducted using VOSviewer and Bibliometrix to examine publication trends, influential articles, collaboration networks, and keyword co-occurrence patterns. The results indicate a growing global interest in this topic, with publication output peaking in 2021. Research productivity is dominated by countries such as the United States, Australia, and the United Kingdom. Keyword mapping shows that dominant research themes include feeding practices, parenting styles, nutrition, and childhood obesity, highlighting the important role of parents in shaping children’s dietary behaviors and nutritional status. Emerging topics such as the influence of social media, the role of fathers, and broader socio-environmental factors remain relatively underexplored. These findings highlight the need for more interdisciplinary and context-sensitive research to support effective family-based nutrition interventions and evidence-based public health policies.